Pengembaraan Ilmiah ke Mesir, Kajian terhadap Arah Kecenderungan al-Dzahabi dalam Aktivitas Belajar - Misbah, Muhammad Ma'ruf (Fakultas Adab dan Humaniora UIN Raden Fatah, 2024)
Al-Dzahabi is a Syrian scientist who was born in the Hijri 7th century. His odyssey to Egypt to study has contributed to leading him to become a scientist, including becoming a historian. His tendency to odyssey to Egypt to study is a phenomenon that can be analyzed in a historical perspective. Therefore, the approach used in this study is the historical approach. Data collection was carried out using the library research method. Data analysis is carried out by analyzing historical information contained in its various sources, which are related to historical events that become the object of research. The research results show the existence of a phenomenon that Egypt was able to act as a destination for a scientific odyssey in studying activities so that it can attract al-Dzahabi's interest to odyssey to the country to study as part of the direction of his tendency in carrying out scientific activities. On the other side, al-Dzahabi's enthusiasm for studying was very high, so he was able to carry out his interests. The phenomenon of Egypt as a center of study which became a destination for a scientific odyssey in studying activities at his time was marked by the number of scientists who became teachers in the country and the number of students who visited the country to study. Thus, Egypt was able to create a scientific atmosphere. In conclusion, Egypt has become an attraction for al-Dzahabi to serve as a destination for a scientific odyssey in search of knowledge. Keywords: al-Dzahabi; scientist; Egypt; scientific odyssey.